The influence of Google Sites on improving students’ vocabulary mastery - Lucia, Waredayani Anisa; Siminto, Siminto; Normuliati, Sri (Journal of Research on English and Language Learning (J-REaLL), 2024)
Language skills are crucial for communication and human learning, with vocabulary being essential for accurate writing, reading, and expression of view, and learning, especially for students. Research conducted by Ulinuha and Parnawati (2023) shows that students gave their perception that reading websites does not spend their time during learning and is very enjoyable because this provides meaningful experiences and more interesting than classroom activities. Departing from this, the researcher conducted further research on the influence of Google Sites on improving students’ vocabulary mastery. The participants of this study were 50 students from two different classes at MA Darul Ulum Palangka Raya (classes XI A and XI D). The experimental group was given treatment using Google Sites, while the control group was given treatment using the lecture method. In this study quasi-experimental design and quantitative methods were used. The average pretest score for the experimental class was 72.20, the average posttest score was 83.60. Meanwhile, the control group had an average pretest score of 74.00 and an average posttest score of 81.60. The experimental class's average achievement vulnerability improved by 11.4 points, compared to 7.6 points in the control class. The result shows that students found it easier to master vocabulary better by using Google Sites as a learning media and proves that treatment using Google Sites media can encourage students' excitement or interest in learning to achieve better results. The implication of the research was choosing the right learning media can affect students' learning achievement, especially in mastering vocabulary.